Things We've Learnt About Memory - Sellen, Abigail; Banks, Richard; Taylor, Alex (Things We've Learnt About, 2012)
“Things We’ve Learnt About..” is a publication from the Human Experience & Design team that summarises our work around a specific theme in a way that we hope is interesting, insightful and inspirational. And most importantly, succinct.